Effectiveness of Weed Control on Two Varieties of Corn (Zea Mays L.) in West Aceh Regency - Ernawati, Ernawati; Baidhawi, Baidhawi; Jamidi, Jamidi (International Journal of Engineering, Science and Information Technology, 2024)
This research aims to find out which weed control techniques are most effective in suppressing weed growth on corn plants, to find out the interaction of manual, mechanical, and chemical weed control on corn plants, to find out the influence of weed control techniques on the production and growth of corn plants. This research be carried out in West Aceh Regency on corn farming land in the Pante Ceureumen District. The time allocation is from April to June 2014. The research was conducted using a randomized block design with a factorial pattern with two factors being studied. The first factor is the weed control technique (T): no control, manual control, using husk charcoal, chemical, atrazine + mesotrion 1.35 ml each 9 m² and the second factor is the variety (V): Bisi-2 and Bisi-18. Based on the treatment of 12 plots with 3 repetitions times until there are 36 experimental units. Each treatment plot measures 300 cm x 300 cm with a planting distance of 75 cm x 25 cm so that the number of sample plants in each plot is 48 plants and the number of sample plants in each plot is 8 plants. The distance between plots is 50 cm and the distance between replications is 100 cm. The results obtained from observations are analyzed using the F test. If the results obtained from the variance are significantly different at the 5% level. The result of the research that has been carried out is that the most effective control technique in suppressing weed growth in corn plants is found at T5 (chemistry, topramezone + atrazine 1.35 ml each 9 m², at 21, 40, and 56 HST), followed by T2 (culture technique using rice husk charcoal), T4 (Chemical, nicosulfuron + atrazine 1.35 ml each 9 m², at 21, 40, and 56 HST) and T1 (manual, at 21, 40, and 56 HST) have the same position, then T3 (chemistry, atrazine + mesotrione 1.35ml each 9 m², at 21, 40 and 56 HST), and the last position in weed control techniques is WC (without control).